Comparison of haematological parameters of Oreochromis niloticus in Embarkadero River Tanauan, Leyte, Philippines - Dañal, Jo Anne Joy M.; Cabansag, Jerome Benedict P. (2012)
The effects of river quality on the haematological parameters in Oreochromis niloticus (Nile Tilapia) was investigated from February 20, 2012 to March 5, 2012. A total of 50, 3-4 months old adult male Nile Tilapia (100-400 grams) were collected at BFAR Hatchery Babatngon, Leyte and acclimatized at Tanauan Tilapia Hatchery for one month. Thirty six fish samples were exposed in 6 established stations along Embarkadero River, Tanauan, Leyte for 15 days, while another 6 fish individuals were placed at Tanauan Tilapia Hatchery as control group. Water analyses were done 4 times during the 15-day exposure. A significant difference (p<0.05) was observed with temperature, pH, salinity, and dissolved oxygen among the six stations and pond, while no significant difference was observed for turbidity level. For the haematological analyses, a significant reduction (p<0.05) was observed in the Packed Cell Volume (PCV) and Red Blood Cell (RBC) Count. Fish samples from Station 6 had the lowest PCV value with a mean of 17% + or - 2.76 while fish samples from the control group had the highest PCV value of 29% + or - 2.76. Increased values of White Blood Cell (WBC) Count were observed in fish samples exposed to Embarkadero River compared to those fish samples at Tilapia Hatchery. Differential cell counts revealed cell counts revealed Lymphocytes to be the most abundant white blood cell type in the samples ranging from 46% to 90%. No basophils and eosinophils were found in the blood smears. Changes observed in the haematological parameters could indicate stress in the exposed fish samples.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.
Keywords: Oreochromis niloticus -- Comparison of haematological parameters -- Philippines -- Embarkadero River, Tanauan, Leyte